Local Wisdom Through Online Short Story Literacy as a Means of Marine Conservation - Afandi, Iswan; Anshari, Anshari; Agussalim AJ, Andi; Juanda, Juanda (Pelopor Publikasi Akademika, 2024)
On the one hand, the condition of our marine ecosystem is degraded. On the other hand, the existence of social changes in society has caused local wisdom to almost be forgotten by the history of its existence. Therefore, this study aims, namely: 1) to describe the problem of damage to marine ecosystems in Jemmy Piran's four short stories, and 2) to describe the local wisdom in the short story by Jemmy Piran as an alternative for marine conservation. This research used qualitative type with descriptive method. The focus of the research is the problem of damage to marine ecosystems, local wisdom, and marine conservation alternatives in the short stories studied. The theory used is the theory of literary ecology, local wisdom theory, and concepts related to marine conservation. Sources of research data, namely four short stories by Jeremy Piran which can be accessed online via the web ruangsastra.com. The research data are sentences or expressions in the short story that show the problem of marine damage, local wisdom, and marine conservation alternatives in the short story. The analysis technique used is content analysis. The results of the research are: (1) the issue of marine damage due to trash, trawling, and the use of fish bombs; (2) local wisdom found data regarding: 1) ethics totaling 3 data; 2) customary law totaling 6 data; 3) trust totaling 33 data; and 4) the norm is 5 data.